2005
DOI: 10.1385/bter:106:3:231
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Decreases of Calcium, Phosphorus, Sulfur, and Zinc in the Cardiac Valves of Monkeys

Abstract: To elucidate compositional changes of the cardiac valves in monkey with aging, the authors investigated age-related changes of elements in the four cardiac valves of rhesus and Japanese monkeys and the relationships among elements by inductively coupled plasma-atomic emission spectrometry (ICP-AES). The four cardiac valves of the aortic, pulmonary, mitral, and tricuspid valves were resected from 19 rhesus and 11 Japanese monkeys, ranging in age from 10 d to 33 yr. The element contents were determined by ICP-AE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…As the P content decreases in the LCF, the Ca, S, and Mg contents also decrease in the LCF, namely, as the active cell density of the connective tissue cells decreases in the LCF, such proteins as collagen also decrease in the LCF. Similarly significant direct correlations among the Ca, P, S, and Mg contents were also found in the four cardiac valves of monkeys which were composed mainly of the connective tissue [2].…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…As the P content decreases in the LCF, the Ca, S, and Mg contents also decrease in the LCF, namely, as the active cell density of the connective tissue cells decreases in the LCF, such proteins as collagen also decrease in the LCF. Similarly significant direct correlations among the Ca, P, S, and Mg contents were also found in the four cardiac valves of monkeys which were composed mainly of the connective tissue [2].…”
Section: Discussionsupporting
confidence: 53%
“…It was found that in all of the four cardiac valves, cardiac walls of the left and right atria and ventricles, and sinoatrial nodes of monkeys, the P content decreased significantly in childhood. The manners of age-related changes of the P content were very similar between the LCF and four cardiac valves, which were composed mainly of the connective tissue [2].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The authors previously investigated age-related changes of element contents in the four cardiac valves [38], sino-atrial nodes [39], and atrial and ventricular walls [40] of rhesus and Japanese monkeys and found that the Ca and P content decreased in all of the cardiac Fig. 8 Comparison in the average content of Ca between the coronary arteries of Japanese and Thai by age group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors previously investigated age-related changes of elements including P in the SAN [7], cardiac walls [8], cardiac valves [9], and coronary arteries [10] of monkeys without distinction of sex. In all of the SANs, cardiac walls of the left and right atrial walls, left and right ventricular walls, and interatrial and interventricular septa, mitral valves, and left coronary arteries of monkeys, the P content decreased significantly with development and aging.…”
Section: Introductionmentioning
confidence: 99%